An introduction to sieve methods and their applications - Cojocaru, Alina (London Mathematical Society student texts, 2005)
This book provides a motivated introduction to sieve theory. Rather than focus on technical details which obscure the beauty of the theory, the authors focus on examples and applications, developing the theory in parallel. Suitable for a senior level undergraduate course or an introductory graduate course in analytic number theory.